A smartphone application for dispatch of lay responders to out-of-hospital cardiac arrests. (May 2018) - Berglund, Ellinor; Claesson, Andreas; Nordberg, Per; Djärv, Therese; Lundgren, Peter; Folke, Fredrik; Forsberg, Sune; Riva, Gabriel; Ringh, Mattias
Abstract: Background: Dispatch of lay volunteers trained in cardiopulmonary resuscitation (CPR) and equipped with automated external defibrillators (AEDs) may improve survival in cases of out-of-hospital cardiac arrest (OHCA). The aim of this study was to investigate the functionality and performance of a smartphone application for locating and alerting nearby trained laymen/women in cases of OHCA. Methods: A system using a smartphone application activated by Emergency Dispatch Centres was used to locate and alert laymen/women to nearby suspected OHCAs. Lay responders were instructed either to perform CPR or collect a nearby AED. An online survey was carried out among the responders. Results: From February to August 2016, the system was activated in 685 cases of suspected OHCA. Among these, 224 cases were Emergency Medical Services (EMSs)-treated OHCAs (33%). EMS-witnessed cases (n = 11) and cases with missing survey data (n = 15) were excluded. In the remaining 198 OHCAs, lay responders arrived at the scene in 116 cases (58%), and prior to EMSs in 51 cases (26%). An AED was attached in 17 cases (9%) and 4 (2%) were defibrillated. Lay responders performed CPR in 54 cases (27%). Median distance to the OHCA was 560 m (IQR 332–860 m), and 1280 m (IQR 748–1776 m) via AED pick-up. The survey-answering rate was 82%. Conclusion: A smartphone application can be used to alert CPR-trained lay volunteers to OHCAs for CPR. Further improvements are needed to shorten the time to defibrillation before EMS arrival.